O imperativo do sangue: estratégias e representação social de parentesco em indivíduos adotados - Lima, Carla Kelli Schons de (2013)
Even in contemporary society, apparently unrelated, representations of family and kinship are of great importance in social relationships, remaining impregnated in the common sense the model of the nuclear family, considered ideal, consisting of father, mother and their biological children. In this scenario, the adoption arises, able to promote the plural kinship of the adopted because despite the socio-affective bond resulting from it, remains the biological bond, socially more valued , since it is justified by the discourse of natural and can be claimed in any time. Thus, there is a naturalization of a social construction, which is the kinship, so that it is constructed and then justified by criteria of inclusion or exclusion of its members. So, in families that do not have adopted children, the criteria coincide with the biological, while for families with adopted children, the criterion that defines kinship is extended beyond the biological, revealing the primacy of socialization about the supposed nature. Therefore, the individual adopted constructs his representations of kinship through the experiences and relationships held with adoptive and biological families, manipulating the categories to justify kinship ties, and subjects may experience both ties with greater or lesser intensity, or choose for some of them, which shows the power of agency of the subjects and the possibility of manipulation of kinship and of the categories that define it.